Characterization of JAZ-interacting bHLH transcription factors that regulate jasmonate responses in Arabidopsis - Niu, Yajie (Oxford University Press, 2011)
The plant hormone jasmonate (JA) plays important roles in the regulation of plant defence and development. JASMONATE ZIM-DOMAIN (JAZ) proteins inhibit transcription factors that regulate early JA-responsive genes, and JA-induced degradation of JAZ proteins thus allows expression of these response genes. To date, MYC2 is the only transcription factor known to interact directly with JAZ proteins and regulate early JA responses, but the phenotype of myc2 mutants suggests that other transcription factors also activate JA responses. To identify JAZ1-interacting proteins, a yeast two-hybrid screen of an Arabidopsis cDNA library was performed. Two basic helix-loop-helix (bHLH) proteins, MYC3 and MYC4, were identified. MYC3 and MYC4 share high sequence similarity with MYC2, suggesting they may have similar biological functions. MYC3 and MYC4 interact not only with JAZ1 but also with other JAZ proteins (JAZ3 and JAZ9) in both yeast two-hybrid and pull-down assays. MYC2, MYC3, and MYC4 were all capable of inducing expression of JAZ::GUS reporter constructs following transfection of carrot protoplasts. Although myc3 and myc4 loss-of-function mutants showed no phenotype, transgenic plants overexpressing MYC3 and MYC4 had higher levels of anthocyanin compared to the wild-type plants. In addition, roots of MYC3 overexpression plants were hypersensitive to JA. Quantitative real-time RT-PCR expression analysis of nine JA-responsive genes revealed that eight of them were induced in MYC3 and MYC4 overexpression plants, except for a pathogen-responsive gene, PDF1.2. Similar to MYC2, MYC4 negatively regulates expression of PDF1.2. Together, these results suggest that MYC3 and MYC4 are JAZ-interacting transcription factors that regulate JA responses.